Exploring the Training of Film and Video Talents in Higher Vocational Colleges under the Background of AIGC - Wang, Fu (Journal of Educational Research and Policies, 2024)
With the rapid development of Artificial Intelligence Generated Content (AIGC) technology, the film and video industry's production process and creation mode are profoundly transforming. This technological advancement has put forward new requirements for film and video talent cultivation in higher vocational colleges, prompting the education system to make targeted optimisation in key areas such as curriculum, practical teaching, teacher construction and school-enterprise cooperation. Based on the talent demand of the film and video industry in the context of AIGC, this study analyses the main challenges facing film and Video education in higher vocational colleges, including the disconnection between the curriculum content and the development of the industry, the insufficiency of practical teaching resources, and the weakness of the faculty. Because of these problems, the study proposes the strategies of building an interdisciplinary curriculum system, strengthening practical teaching, deepening university-enterprise cooperation and improving the ‘dual-teacher’ teaching team to provide effective references for the cultivation of high-quality film and video talents with innovative ability and practical skills in higher vocational colleges.